2022
DOI: 10.48550/arxiv.2205.03424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A deep near-infrared view of the Ophiuchus galaxy cluster

D. Galdeano,
G. Coldwell,
F. Duplancic
et al.

Abstract: Context. The Ophiuchus cluster of galaxies, located at low latitudes in the direction of the Galactic bulge, has been relatively poorly studied in comparison with other rich galaxy clusters, such as Coma, Virgo, and Fornax, despite being the second brightest X-ray cluster in the sky. Aims. Our aim is perform a study of the hidden galaxy population of the massive cluster Ophiuchus located in the Zone of Avoidance. Methods. Deep near-infrared images and photometry from the VISTA Variables in the Vía Láctea eXten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…3.1. This result is consistent with what was found by Baravalle et al (2019) and Galdeano et al (2022) for other galaxy clusters studied using the VVV survey.…”
Section: Red Sequencesupporting
confidence: 93%
See 1 more Smart Citation
“…3.1. This result is consistent with what was found by Baravalle et al (2019) and Galdeano et al (2022) for other galaxy clusters studied using the VVV survey.…”
Section: Red Sequencesupporting
confidence: 93%
“…In addition, Baravalle et al (2019) confirmed the existence of the first galaxy cluster, discovered by the VVV survey beyond the galactic disk, by using spectroscopic data from the spectrograph Flamingos 2 (hereafter F2) at Gemini South Observatory. More recently, Galdeano et al (2022) present an NIR view of Ophiuchus, the second-brightest galaxy cluster in the X-ray sky, finding seven times more cluster galaxy candidates than the number of reported Ophiuchus galaxies in previous works.…”
Section: Introductionmentioning
confidence: 84%
“…3.1. This result is consistent with that found by Baravalle et al (2019) and Galdeano et al (2022) for other galaxy clusters studied using the VVV survey.…”
Section: Red Sequencesupporting
confidence: 93%